Tibial Plateau Levelling Osteotomy in Cats: A Retrospective Study of 23 Cases - Frizzi, Massimo; Ballarini, Laura; Gaio, Daniele (VCOT Open, 2025)
This study aimed to describe tibial plateau levelling osteotomy procedures in cats with cranial cruciate ligament ruptures, assessing related complications (intra- and postoperative) and long-term outcomes after mini/micro-FIXIN T/L plate stabilizations.The study design was retrospective.A total of 23 cats with cranial cruciate ligament ruptures were selected, each undergoing general and orthopaedic clinical assessments and subjected to tibial plateau levelling osteotomy procedures, with simultaneous exploratory mini-arthrotomies. We collected medical histories and reporting data, complete blood and urine test results and imaging diagnostics (echocardiography, radiography under sedation). Remnant cranial cruciate ligament histology was available on seven occasions. Follow-up orthopaedic examinations and radiographs were done at postoperative months 1, 2, 4, 6, 12, and 24.The overall complication rate was 24% (inadequate compression of osteotomy surfaces, 2; fibula fracture, 3; breakage of screws and tibial crest, 1), only one event (4%) being major. Concomitant medial meniscal injury was evident in 76% of joints. During 24 months of follow-up, all patients fully recovered, without recurrences or significant osteoarthritic deterioration.Preliminary study results indicate that tibial plateau levelling osteotomy procedures in feline species confer good long-term limb function, with minimal progression of osteoarthritis.
Keywords: TPLO; cranial cruciate ligament rupture; meniscal lesion; 24-month follow-up; cat